Does your SOA include a persistence strategy? you need to consider the nonvolatile along with the volatile. - Linthicum, David
Truth be told, traditional approaches to integration are really about keeping persistence at the points, within the source or target systems and replicating data as needed. However with the use of true services, there is a clear advantage in keeping some persistence at a central-tier, for any number of legitimate reasons. Let's explore this in the context of an SOA.